Research on the Spatial Impact of Green Finance on the Ecological Development of Chinese Economy - Wu, Guosong (Frontiers in Environmental Science, 2022)
Carbon peaking and carbon neutralization have become catalysts for the development of green finance in China. The possible risks of climate change are also being considered by an increasing number of financial institutions. Environmental pollution and deterioration have become the main drivers of China’s unbalanced and insufficient development in the new era. As a new financial model, green finance has attracted much attention from people and the society. Promoting and integrating this concept into economic transformation and ecological civilization strategies can guarantee China’s high-quality green development through economic ecology. This paper analyzes the relationship between the development of green finance and the development of economic ecology. The research conclusion is of great significance to speed up the construction of ecological civilization in China.Firstly, this paper analyses the spatial correlation between green finance and economic ecological development in China using the Moran’s index. Secondly, this paper constructs a spatial econometric model and performs a regression empirical analysis using the panel data of 30 provinces in China from 1999 to 2020 to understand the impact of green finance on China’s ecological development. Results show that green finance demonstrates strong spatial agglomeration and that the development of economic ecology maintains a stable spatial positive correlation. Moreover, the spatial difference in economic ecological development is more obvious than that in green finance development. The development of green finance not only has a significantly positive role in promoting the economic and ecological development of a certain province but also promotes the development of economic ecology in the surrounding provinces. The development of economic ecology itself generates a positive spatial spillover effect, that is, improving the economic ecological level of a province will also improve the corresponding level of the surrounding provinces.